2016
DOI: 10.9775/kvfd.2015.13114
|View full text |Cite
|
Sign up to set email alerts
|

Şap Hastalıklı Boğalarda Serum ve Salya Sialik Asit ve Oksidatif Stres Parametrelerindeki Değişiklikler

Abstract: The study comprised of 12 bulls, aged between 18-36 months, determined severe symptoms of Foot-and-mouth disease (FMD) and 10 clinically healthy bulls of similar age. Serum and saliva total sialic acid (SA), malondialdehyde (MDA), glutathione (GSH) and nitric oxide (NO) levels were measured. In this study were determined acute fever, anorexia, vesicular lesions in the mouth and feet of infected animals with consequent excessive salivation, lameness and reduced productivity as clinical signs. Mean serum SA, MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Saliva is a biological fluid and can be collected non-invasively [5] . Uzlu et al [6] measured some oxidative stress parameters (MDa, glutathione and NO) and total sialic acid levels in serum and saliva samples taken from bulls infected with foot and mouth disease, and determined that significant alterations had occurred in both the salivary and serum levels of these parameters. In a previous medical study performed in patients with oral squamous cell carcinoma, the measurement of salivary interleukin-1 alpha, interleukin-6, interleukin-8 and granulocyte macrophage-colony stimulating factor levels demonstrated that these parameters significantly differed between the patients and the control group [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva is a biological fluid and can be collected non-invasively [5] . Uzlu et al [6] measured some oxidative stress parameters (MDa, glutathione and NO) and total sialic acid levels in serum and saliva samples taken from bulls infected with foot and mouth disease, and determined that significant alterations had occurred in both the salivary and serum levels of these parameters. In a previous medical study performed in patients with oral squamous cell carcinoma, the measurement of salivary interleukin-1 alpha, interleukin-6, interleukin-8 and granulocyte macrophage-colony stimulating factor levels demonstrated that these parameters significantly differed between the patients and the control group [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Saliva, which is a continuously produced secretion, is being used for analyses in human medicine [5] . In veterinary medicine, saliva samples have been used for the measurement of total sialic acid levels and oxidative stress parameters (malondialdehyde (MDa), glutathione, nitric oxide (NO)) in cattle [6] , Saa [7,8] , Hp [8][9][10] , cortisol [8] , interleukin-18 (IL-18) [11] , and C-reactive protein (CRP) [9,10,12] levels in pigs and CRP levels in dogs [5] . However, veterinary research in this field is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased formation of free radicals and lipid peroxidation develops the oxidative stress. Oxidative stress might be estimated with malondialdehyde, sialic acid, total oxidant capacity and total antioxidant capacity [5] .…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism is also valid for tumour cells. Therefore, NO is considered to be a component of non-specific immunity [30,[33][34][35] . In the present study, the serum NO levels of the stereotypic animals were found to be higher than those of the healthy animals (P<0.001).…”
Section: Discussionmentioning
confidence: 99%